BRCA1 and BRCA2 Mutations Other Than the Founder Alleles Among Ashkenazi Jewish in the Population of Argentina - Solano, Angela R.; Liria, Natalia C.; Jalil, Fernanda S.; Faggionato, Daniela M.; Mele, Pablo G.; Mampel, Alejandra; Cardoso, Florencia C.; Podesta, Ernesto J. (Frontiers in Oncology, 2018)
The Ashkenazi Jewish population presents a routine 3-mutation panel, 2 in BRCA1 (c.68_69del and c.5266dup) and 1 in BRCA2 (c.5946del), which severely increase the risk of breast and ovarian cancer among other less frequent types. Beyond these cases, there is little information about patients who do not carry one of these founder mutations and obtaining more data would be valuable to the patient and family for cancer prevention and treatment. In this study, 279 Jewish individuals were received at CEMIC, and genomic DNA from all probands was sequenced for the Ashkenazi panel. Out of the 279 probands (259 of them women), 55 (50 of them women) bore one of the 3 mutations (19.7%); 76 individuals (73 of them women) who tested normal for the panel were subsequently analyzed by NSG (Next Generation Sequencing) and large rearrangements of both genes for the full coding sequence looking for mutations beyond the panel. Of these 76 probands, 6 (7.9%) carried a pathogenic mutation, as follows: in BRCA1, c.2728C>T - p.(Gln910*); c.5407-?_(*1_?)del and c.5445G>A - p.(Trp1815*); in BRCA2, c.5351dup - p.(Asn1784Lysfs*3); c.7308del - p.(Asn2436Lysfs*33) and c.9026_9030del - p.(Tyr3009Serfs*7). BRCA2 mutation c.5351dup was detected in the only men from a total of three fully sequenced by NGS. In patients with a mutation detected, the youngest age at diagnosis was 28 years (breast cancer: 41.6±9.3 years) in a woman with breast cancer, while the oldest were observed in a patient with ovary cancer at 77 years (ovary cancer: 60.57±13.3 years) and a man with breast cancer at 76 years (men-breast cancer: 61.5±20.5 years). All 61 individuals bearing a BRCA1 or BRCA2 mutation had a personal or family history of breast/ovarian cancer and/or related cancers, including 11 healthy individuals. This information proved highly useful for counseling, treatment and prevention for the patient and the family. In conclusion: comprehensive BRCA1/2 testing should follow the panel of three mutations with normal sequence report to provide complete relevant genetic information for Ashkenazi Jewish patients with breast/ovary cancer, related cancer or family history.